Legal Reconstruction Settlement Of Sharia Capital Market Disputes: Strengthening Regulatory Aspects To Provide Legal Certainability - Habib Rasyidi Daulay (International Journal Reglement & Society (IJRS), 2021)
Regulations regarding the Islamic capital market follow the rules contained in Law 8/1995 concerning Capital Market, MUI DSN Fatwa Number 40 / IX / 2003, Bapepam and LK Regulations Number IX, A, 13, Number IX, A, 14, and Number ILKL. Of the several rules, none have clearly regulated the settlement of Islamic capital market disputes, either by litigation or non-litigation, which has resulted in a legal vacuum (leemten in het recht). The provisions for the settlement of sharia economic disputes, including the Islamic capital market disputes, are only found in Law 3/2006. Through quantitative research methods, this research seeks to harmonize the empty rules as well as to fill the legal gaps. The research concludes that the settlement of Islamic capital market disputes by litigation is resolved in religious courts, while non-litigation is resolved through BASYARNAS and / or as other civil disputes can also be resolved through alternative dispute resolution in accordance with Law 30/1999.